Students’ online interaction, self-regulation, and learning engagement in higher education: The importance of social presence to online learning - Miao, Jia; Ma, Li (Frontiers in Psychology, 2022)
Online learning has become an essential part of acquiring academic and professional qualifications in higher education. Online learning recently gained attention as an effective instructional approach to enhance learning engagement, causing many universities to implement it. To promote learning engagement in online learning environments in higher education, this study collected data from 334 full-time undergraduate students in a large public Chinese university and examined the effects of online interaction, self-regulation and social presence on learning engagement. The research findings indicated that online interaction affected social presence and indirectly affected learning engagement through social presence. In addition, social presence affected learning engagement, self-regulation affected social presence, and social presence also mediated the relationship between self-regulation and learning engagement. This study confirmed the significant effects of self-regulation and social presence on students’ learning engagement in online environments. The findings of this study have significant practical implications for teaching practices.